Studi Deskriptif Entrepreneurial Resilience pada Wirausahawan Mahasiswa di Masa Pandemik Covid-19 - Muhammad Rizki Pratama; Oki Mardiawan (UNISBA Press, 2022)
Abstract. Entrepreneurial resilience is one of the most important skills needed by entrepreneurs in dealing with difficult situations that occur in their environment (Ayala & Manzano, 2014). One of these difficult situations is the Covid-19 pandemic which is not only felt by adult entrepreneurs and has been doing entrepreneurial activities for a long time, but the negative impact of the Covid-19 pandemic is also felt by student entrepreneurs and just starting their business. Therefore, when in difficult conditions such as the Covid-19 pandemic, a student entrepreneur needs resilience skills to be able to get through these difficult situations (Linnenluecke, 2017). The purpose of this study was to get an overview of Student Entrepreneurial Resilience in the Covid-19 Pandemic Period. In addition, in this study, researchers also want to see differences in entrepreneurial resilience between sexes and duration of entrepreneurship. In this study, researchers used the concept of Ayala & Manzano (2014) regarding entrepreneurial resilience. This research was conducted on 74 students of the Islamic University of Bandung who have had a minimum of 1 year of entrepreneurship and felt the impact of the Covid-19 pandemic. The measuring instrument used is the entrepreneurial resilience scale from Ayala & Manzano (2014) which then after being tested for validity and reliability, there are 21 items. The results of this study indicate that entrepreneurial resilience tends to be in the high category of student entrepreneurs at the Islamic University of Bandung. Abstrak. Entrepreneurial resilience menjadi salah satu kemampuan penting yang diperlukan wirausahawan dalam menghadapi adanya situasi sulit yang terjadi di lingkungannya (Ayala & Manzano, 2014). Salah satu situasi sulit tersebut adalah pandemik Covid-19 yang bukan hanya dirasakan oleh wirausahawan usia dewasa dan sudah lama melakukan kegiatan wirausaha, namun dampak negatif dari pandemik Covid-19 juga dirasakan oleh wirausahawan mahasiswa dan baru memulai bisnis mereka. Oleh karena itu ketika berada di kondisi sulit seperti pandemik Covid-19 seseorang wirausahawan mahasiswa memerlukan kemampuan resiliensi untuk dapat melewati situasi sulit tersebut (Linnenluecke, 2017). Tujuan dari penelitian ini adalah untuk mendapatkan gambaran mengenai Entrepreneurial Resilience Wirausahawan Mahasiswa di Masa Pandemik Covid-19. Selain itu pada penelitian ini juga peneliti juga ingin melihat perbedaan entrepreneurial resilience antar jenis kelamin dan lamanya berwirausaha. Pada penelitian ini, peneliti menggunakan konsep Ayala & Manzano (2014) mengenai entrepreneurial resilience. Penelitian ini dilakukan pada 74 orang mahasiswa Universitas Islam Bandung yang telah memiliki wirausaha minimal 1 tahun dan merasakan dampak dari pandemik Covid-19. Alat ukur yang digunakan adalah skala entrepreneurial resilience dari Ayala & Manzano (2014) yang kemudian setelah dilakukan uji validitas dan realibilitas berjumlah 21 item. Hasil penelitian ini menunjukan bahwa entrepreneurial resilience cenderung berada di kategori yang tinggi pada wirausahawan mahasiswa Universitas Islam Bandung.